2009
DOI: 10.1007/s12026-009-8113-x
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of direct TLR signaling to T cell responses

Abstract: It is well established that Toll-like receptors (TLRs) play a critical role in the generation of innate immune responses and thereby also play an important, indirect role in the initiation of subsequent adaptive T cell responses. However, T cells also express certain TLRs, and we have focused on the physiological importance of direct TLR signaling in T cells. TLRs can function as co-stimulatory receptors that complement TCR-induced signals to enhance effector T cell proliferation, survival and cytokine product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 55 publications
4
102
1
3
Order By: Relevance
“…Another possibility is that TLR signaling by CpG ODN may directly costimulate T cells. CD8 + T cells are known to express TLR-9, and direct stimulation through intrinsic TLRs is recognized as a significant factor in T cell modulation (for review, see reference [23]). Interestingly, Zhong et al reported that direct stimulation of purified primary mouse B cells using CpG ODN can downregulate PD-1 expression, raising the possibility that a similar mechanism may occur in T cells [24].…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that TLR signaling by CpG ODN may directly costimulate T cells. CD8 + T cells are known to express TLR-9, and direct stimulation through intrinsic TLRs is recognized as a significant factor in T cell modulation (for review, see reference [23]). Interestingly, Zhong et al reported that direct stimulation of purified primary mouse B cells using CpG ODN can downregulate PD-1 expression, raising the possibility that a similar mechanism may occur in T cells [24].…”
Section: Discussionmentioning
confidence: 99%
“…The latter group includes stimuli such as heat shock proteins, hyaluronan, fibronectin, heparin and surfactant protein A, which have been reported to activate Tlr2 and Tlr4 (14,15). As the development of fibrotic lung disease can involve the excessive deposition of fibronectin (16) or can occur through mutations in surfactant protein A (17), it is possible that altered signaling through Tlrs may be a component of radiation-induced fibrotic lung disease.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, our preliminary results showed that Imiquimod, another TLR7 ligand 30 , suppressed CD4 + T cell proliferation of murine CD4 + T cells stimulated with anti-CD3e/CD28 mAb. Although these two results seem to be conflicting, we think that this difference would be caused by the differences in the experimental settings, such as using different TLR ligands, Resiquimod and Imiquimod, and using human or murine T cells.…”
Section: Discussionmentioning
confidence: 69%
“…30 The anti-oxidant NAC is commonly used for its ability to minimize intracellular oxidative stress. In this study, NAC abrogated the suppressive effect of both LG2809 and its RNA, which suggests that ROS are involved in this effect.…”
Section: Discussionmentioning
confidence: 99%